2019
DOI: 10.2147/idr.s203661
|View full text |Cite
|
Sign up to set email alerts
|

<p>Whole-genome sequence analysis of multidrug-resistant uropathogenic strains of <em>Escherichia coli</em> from Mexico</p>

Abstract: Background : Escherichia coli is the main bacterium associated with urinary tract infections (UTIs), including cystitis and pyelonephritis. Uropathogenic E. coli (UPEC) harbors numerous genes that encode diverse virulence factors contributing to its pathogenicity. The treatment of UTIs has become complicated due to the natural selection of E. coli strains that are multiresistant to several groups of antibiotics regularly used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Resistant isolates (2020) 10:8754 | https://doi.org/10.1038/s41598-020-65602-z www.nature.com/scientificreports www.nature.com/scientificreports/ often have multiple mutations and it can be difficult to determine true differences in a clinical isolate with an unknown parental strain. Moreover, high-level multi-drug resistant clinical isolates are often tested for mutations in distinct gene clusters specific to various antibiotics 57,58 , which may miss single nucleotide changes outside these regions which are related to broader, non-specific mechanisms of resistance. It is also possible that first-step mutations which allow for additional mutations for increased resistance or fitness are lost during selection at high treatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant isolates (2020) 10:8754 | https://doi.org/10.1038/s41598-020-65602-z www.nature.com/scientificreports www.nature.com/scientificreports/ often have multiple mutations and it can be difficult to determine true differences in a clinical isolate with an unknown parental strain. Moreover, high-level multi-drug resistant clinical isolates are often tested for mutations in distinct gene clusters specific to various antibiotics 57,58 , which may miss single nucleotide changes outside these regions which are related to broader, non-specific mechanisms of resistance. It is also possible that first-step mutations which allow for additional mutations for increased resistance or fitness are lost during selection at high treatment levels.…”
Section: Discussionmentioning
confidence: 99%
“…From the analysis, it is evident that as the V. parahaemolyticus genomes accumulated, the number of core genes reduced while the number of pan genes increased. This demonstrates the versatility of V. parahaemolyticus open pan-genome, which is a characteristic feature for bacteria with the capability to acquire new genes via HGT [ 58 , 59 ]. The open pan-genome also illustrates the diversity in the V. parahaemolyticus genome within the species.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggests that the genetic variability promoted by IS21 and IS3 could have an important role in the formation of resistance islands. Interestingly, a recent study has reported UPEC strains in Mexico containing Tn21 with similar MDR cassette, but integrated in resistance islands in the chromosome (Paniagua-Contreras et al, 2019 ). In this context, our work supports the hypothesis that pBH100 and other related R100 plasmids might be involved for MDR spreading through the development of Resistance Islands alternatively to conjugation mechanisms.…”
Section: Resultsmentioning
confidence: 99%